Evaluation of Rivaroxaban Exposure via Anti-Xa Levels During VTE Prophylaxis in Hospitalized Patients - Kaitlin Blotske PharmD; Toral Patel PharmD, BCPS; Toby Trujillo PharmD, FCCP, FAHA, BCPS; Matthew Marlar MLS (ASCP); Stuart Lind MD; Henry Kramer MD; Kathryn Hassell MD; Tyree H. Kiser PharmD, FCCM, FCCP, BCCCP, BCPS (Clinical and Applied Thrombosis/Hemostasis)
Rivaroxaban was FDA-approved in 2019 for venous thromboembolism (VTE) prophylaxis in acutely ill hospitalized patients. Little to no published data is available to determine the level of correlation between rivaroxaban drug concentration and UFH/LMWH calibrated anti-Xa assays at VTE prophylactic doses of rivaroxaban 10 mg daily. This study aimed to assess the anticoagulant effects of rivaroxaban prophylactic doses using LMWH calibrated anti-Xa levels at the University of Colorado Hospital (UCH). This prospective cohort study evaluated seventy-three hospitalized patients at UCH taking rivaroxaban 10 mg daily for VTE prophylaxis from June 2023 to April 2024. Patients were enrolled if they were between the ages of 18-89 years old, received rivaroxaban 10 mg daily, and had active orders for coagulation studies. A linear regression model and coefficient of determination was used to evaluate the primary outcome assessing the relationship between rivaroxaban drug concentrations and anti-Xa levels. The LMWH calibrated anti-Xa assays were strongly correlated to rivaroxaban concentrations ranging from (1-59 ng/ml) in patients receiving rivaroxaban 10 mg daily, r 2  = 0.99 ( P  < .00001). Our data suggests that LMWH calibrated anti-Xa levels less than 1.40 IU/ml may indicate minimal anticoagulation effects for rivaroxaban 10 mg daily. The secondary outcomes assessing the relationship between rivaroxaban drug concentrations and time since administration, r 2  = 0.16 ( P  = .049), as well as time since administration of rivaroxaban and anti-Xa activity, r 2  = 0.15 ( P  = .066), were weakly correlated and showed a trend. Characterizing the high correlation between anti-Xa levels and rivaroxaban plasma concentrations at 10 mg daily doses, provides additional insight to rivaroxaban's anticoagulant effects in clinical practice. This can be beneficial in various clinical scenarios and has the potential to reduce the waiting time for clinical procedures.